KLASIFIKASI WILAYAH RISIKO BENCANA BANJIR DI KOTA SEMARANG DENGAN PERHITUNGAN INDEKS VEGETASI - Adenia Kusuma Dayanthi; Sri Yulianto Joko Prasetyo; Charitas Fibriani (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Land use in an area is influenced by population growth and activities. Changes in land use continuously will cause environmental changes that often trigger an increase in natural disasters. In this study, the assessment was carried out using the calculation of the Normalized Difference Vegetation Index (NDVI), Normalized Difference Wetness Index (NDWI) and Soil Adjusted Vegetation Index (SAVI). The data used came from Landsat OLI 8 imagery data from 2020 to 2023. The results of this study showed that in the range of 2020 to 2023 the changes in the three calculations of the vegetation index were not significant. From the data obtained, the classification for calculations in the rainy and dry seasons was the same, the NDVI vegetation index obtained high vegetation, the SAVI vegetation index obtained forested vegetation, and the NDWI vegetation index obtained high wetness. Overall the assessment of the vegetation index obtained good results, and it can be concluded that not all areas in Semarang City are at risk of flooding, even during the rainy season.